(untitled) (American Journal of Islam and Society, 2009)
The goal of this book “is to provide a way of conceptualizing the Islamic tradition that is different from that proposed by conventional scholarship” (p. 6). The author wants to highlight howMuslims themselves view modernity because their own views have been overshadowed by western scholarship and have problematized assumptions founded on the oppositional dichotomies of modern versus traditional or secular versus sacred. She argues that a tradition is not simply the recapitulation of previous beliefs and practices, but that each successive generation confronts its own particular problems via an engagement with a set of ongoing arguments. Therefore, the author asserts, one effective way of addressing Islam is to approach it as Muslims do – as a discursive tradition embodied in the practices and institutions of their communities. Haj intends to attain her goals and highlights these problems by analyzing the work of two significant Muslim reformers: Muhammad ibn Abd al- Wahhab (1703-87) and Muhammad Abduh (1849-1905). Although they belong to different historical periods and social settings, she feels that their work has inspired the two major strands of contemporary Islamic political thought. The former, an Arabian reformer, has often been referred to as the “legendary mastermind of a ‘fundamentalist’ and ‘violent’ political movement, the inspiration for the present-day militant Muslim groups (like al- Qa`ida) in their struggle against modernity” (p. 30). The latter is an Egyptian reformer regarded as a liberal humanist who underlined the essence of Muslim humanism for the modern world ...